Major depresif bozukluk tedavisinde SSGİ (serotonin geri alım inhibitörü) tedavisine nondominant el çalıştırma görevi eklenmesinin standart tedaviyle istirahat hali (resting state) fonksiyonel manyetik rezonans görüntüleme (rs-f MRI) üzerinden kıyaslamalı çalışması - BOYRAZ, Rabia Kevser (Bezmialem Vakıf University, 2019)
Introduction: Major depressive disorder (MDD) is a mental disorder that contributes greatly to the global burden of disease by the World Health Organizaion (WHO) because of its prevalence in the community, the high likehood of recurrence despite various treatment modalities and the loos of functionality it causes. In MDD, it is seen that the researches have recently shifted from functional and structural imaging studies to functional connectivity studies.

{{abstract}}
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Mental Health and Diseases, Istanbul, 2019
Keywords: Ruh Sağlığı ve Hastalıkları Anabilim Dalı; Department of Mental Health and Diseases; Psikiyatri = Psychiatry; Major Depresif Bozukluk; Major depressive disorder (MDD)